Protective effects of tilapia fish oil and liposomes on ischemia reperfusion injury of rat liver. Issue 6 (19th September 2018) - Lin, Lin; Wang, Qianqian; Lu, Jianfeng; Lv, Shun; Jiang, Shaotong
Abstract: The effects of tilapia fish oil and liposomes containing fish oil on hepatic ischemia/reperfusion (I/R) injury of rats were investigated. The activities of alanine aminotransferase, aspartate aminotransferase, gamma glutamyl transferase and lactate dehydrogenase, and the levels of tumor necrosis factor‐alpha, interleukin‐6, and interleukin‐10 in serum of rats were determined. In addition, the malondialdehyde contents, superoxide dismutase activities, nuclear factor‐kappaB (NF‐кB) activation and the apoptosis in hepatic tissue of rats were estimated. The results showed that the administration of tilapia fish oil and liposomes could reduce the hepatocellular damage, neutrophil infiltration and oxidative stress, decrease inflammatory cytokines, increase antiinflammatory cytokine, and attenuate NF‐кB activation of hepatic I/R injury rats. Overall, the tilapia fish oil and liposomes exerted antiinflammatory and antioxidant effects on ischemic liver, thereby protecting hepatocytes against I/R injury. Practical applications: Fish oil has many dietary benefits, but due to its strong odors and rapid deterioration, its application in food formulations is limited. The encapsulation of fish oil in liposomes is a good choice for reduction of fish odor smell and improvement of oxidative stability. The present study investigated the protective effects of tilapia fish oil and liposomes on hepatic I/R injury of rat. The results showed that both the free tilapia fish oil and its liposomes had antiinflammatory and antioxidant effects on the experimental rats. Therefore, liposomes containing tilapia fish oil should be considered as a prospective functional food and pharmaceuticals application.